Rancang Bangun Buka Kunci Pintu Menggunakan RFID Berbasis Atmega 328 di Master Control Room Ratih TV Kebumen - Wijaya; Asni Tafrikhatin; Ajeng Tiara Wulandari; Asli Husain (JASATEC : Journal Students Of Automotive, Electronic and Computer, 2022)
Most of the workspace door locks use a manual locking system so that it lacks security. The safety of the master control room is a priority, because in the room there are important tools and documents.Based on these problems, the authors made a door lock unlock design using Atmega328-based RFID. This research method is: R & D. design and construction of door unlock using Atmega 328 based RFID. E-ID card attached to the door serves as an input to open the lock. This product is expected to increase safety when using the workspace.